2020
DOI: 10.1016/j.foodchem.2019.125735
|View full text |Cite
|
Sign up to set email alerts
|

Jabuticaba residues (Myrciaria jaboticaba (Vell.) Berg) are rich sources of valuable compounds with bioactive properties

Abstract: Jabuticaba (Myrciaria jaboticaba (Vell.) Berg) is a Brazilian berry, very appreciated for in natura consumption. However, its epicarp is not normally consumed due to its stiffness and astringent taste, and in manufacture of products from jabuticaba fruit, it is responsible for the generation of large amounts of residues. The exploration of by-products is becoming important for the obtainment of valuable bioactive compounds for food and pharmaceutical industries. In this context, jabuticaba epicarp was studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 41 publications
2
44
2
5
Order By: Relevance
“…The concentration of this phenolic compound in S. odorifera epicarp fruit is interesting, since it is more than quantified in other purple fruits, such as jabuticaba (Myrciaria jaboticaba (Vell.) Berg) epicarp (50.1 mg/g E) [23], grape (Vitis vinifera L.) peel (7.9 mg/g E) [24], passion fruit (Passiflora edulis Sims) epicarp (9 mg/g E) [25], juçara (Euterpe edulis Martius) peels (11 mg/g dw) [26], eggplant (Solanum melongena L.) epicarp (11.9 mg/g E) [27], and açai (Euterpe oleracea Mart.) (100 mg/g E) [28].…”
Section: • Anthocyanin Compoundsmentioning
confidence: 99%
“…The concentration of this phenolic compound in S. odorifera epicarp fruit is interesting, since it is more than quantified in other purple fruits, such as jabuticaba (Myrciaria jaboticaba (Vell.) Berg) epicarp (50.1 mg/g E) [23], grape (Vitis vinifera L.) peel (7.9 mg/g E) [24], passion fruit (Passiflora edulis Sims) epicarp (9 mg/g E) [25], juçara (Euterpe edulis Martius) peels (11 mg/g dw) [26], eggplant (Solanum melongena L.) epicarp (11.9 mg/g E) [27], and açai (Euterpe oleracea Mart.) (100 mg/g E) [28].…”
Section: • Anthocyanin Compoundsmentioning
confidence: 99%
“…These compounds have shown promise against bacteria such as Escherichia coli , Streptococcus aureus and Listeria monocytogenes . Furthermore, these compounds have a potential application against tumour cells [220] …”
Section: Fruits and Nuts As Potential Brazilian Renewable Sourcesmentioning
confidence: 99%
“…It is important to state that for the anti-inflammatory assay the maximum tested concentration of the extracts was 184 400 μg/ml. In comparison with other studies, the Rosemary extract showed greater antiinflammatory activity than, for example, Jaboticaba epicarp (IC50 = 299 μg/ml) (Albuquerque, Pereira, et al, 2020). Wahyudi, Ramadhan, Wijaya, Ardhani, & Utami (2020) also demonstrated the anti-inflammatory properties of potato peel extracts by conducting an in vivo study with rats, using carrageenan-induced paw edema and diclofenac as the reference drug.…”
Section: Cell-based Antioxidant and Anti-inflammatory Activitiesmentioning
confidence: 81%
“…In response to that, the food and pharmaceutical industries have been researching the use of natural matrices as sources of compounds with beneficial health effects (Wahyudi, Ramadhan, Wijaya, Ardhani, & Utami, 2020). For this purpose, the valorisation of alternative sources of bioactives (such as novel grains and wild crops) and bio-residues (that are usually discarded but can be rich in bioactive compounds) can contribute to the creation of more economically and socially sustainable productive chains (Albuquerque, Pereira, et al, 2020;. With this aim, the extraction of plant bioactive molecules has been largely explored and well established by many authors as an efficient route for the reutilization of food processing waste, especially when considering the recent technological advances in molecular separations and identifications .…”
Section: Alternative Functional Foods and Additivesmentioning
confidence: 99%